FOREIGN LANGUAGE TEACHING AIDS (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
Foreign Language Teaching Aids (Tools) include traditional items like flashcards, realia (real objects), charts, and whiteboards, alongside modern digital tools such as language apps (Duolingo), interactive whiteboards, AI assistants (ChatGPT), online platforms, and kinesthetic aids like games (Jenga, story cubes) and role-playing to develop skills like listening, speaking, reading, and writing through engaging, context-rich activities.